The Routledge Hispanic studies companion to medieval Iberia
1 online resource (xxiii, 643 pages)
Keywords: "The Routledge Hispanic Studies Companion to Medieval Iberia: Unity in Diversity draws together the innovative work of renowned scholars as well as several thought-provoking essays from emergent academics, in order to provide broad-range, in-depth coverage of the major aspects of the Iberian medieval world. Exploring the social, political, cultural, religious and economic history of the Iberian Peninsula, the volume includes thirty-seven original essays grouped around fundamental themes such as Languages and Literatures, Spiritualities, and Visual Culture. This interdisciplinary volume is an excellent introduction and reference work for students and scholars in Iberian Studies and Medieval Studies"--